2008
DOI: 10.1007/s00424-008-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of mature Xenopus muscle fibres in culture induced by synergy of albumin and insulin

Abstract: The aim of this study was to investigate effects of albumin and insulin separately as well as in combination on mature muscle fibres during long-term culture. Single muscle fibres were dissected from m. iliofibularis of Xenopus laevis and attached to a force transducer in a culture chamber. Fibres were cultured in a serum-free medium at slack length (mean sarcomere length 2.3 μm) for 8 to 22 days. The medium was supplemented with (final concentrations): (1) bovine insulin (6 nmol/L or 200-600 nmol/L), (2) 0.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Quantitative fiber type differentiating approaches obtain insight into interactions between pathways and the integrated effects of different loading programs and stimuli. For example, ex vivo culture systems of mature muscle fibers (Jaspers 2004; Jaspers et al 2008) are well defined and can be used for controlled manipulation of growth factors, mechanical loading and oxygen tension, either independently or in combination. Such approaches may uncover interactions between signal transduction routes, which are to be verified in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative fiber type differentiating approaches obtain insight into interactions between pathways and the integrated effects of different loading programs and stimuli. For example, ex vivo culture systems of mature muscle fibers (Jaspers 2004; Jaspers et al 2008) are well defined and can be used for controlled manipulation of growth factors, mechanical loading and oxygen tension, either independently or in combination. Such approaches may uncover interactions between signal transduction routes, which are to be verified in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mechanical loading-induced expression of local factors, several other components such as albumin, IGF-binding proteins, receptors, cytokines (i.e., TNF-1α, IL-1 and IL-6), calcium and vitamins may modulate the effects of IGF-I and myostatin (Casse et al 2003; Clemmons 1998; Coletti et al 2005; Jaspers et al 2008; Ling et al 1997; Pfeifer et al 2002). For example, insulin receptor phosphorylation, insulin receptor substrate (IRS-2) phosphorylation, as well as the downstream PI3K activity were all shown to be significantly higher in the high oxidative soleus compared to EDL (Song et al 1999).…”
Section: Pathways and Stimuli Regulating Protein Turnover In Differenmentioning
confidence: 99%
“…In addition, differential changes in rat and human GM geometry during growth may be explained by growth factor signalling during development. Recently, studies using ex vivo culture of mature isolated muscle fibres, showed that muscle anabolic growth factors induce radial muscle fibre growth (trophy) without longitudinal growth (Jaspers et al. 2008; Watt et al.…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, serum levels of growth factors are increased (Clark & Rogol, 1996;Rogol et al 2002). For ex vivo cultured mature muscle fibres, such growth factors induce hypertrophy, and no addition of sarcomeres in series (Jaspers et al 2008;Watt et al 2010). Therefore, if elevated serum levels of growth factors are involved in muscle development, their effects are likely to appear as hypertrophy rather than as addition of sarcomeres in series.…”
Section: Introductionmentioning
confidence: 99%